Why volubility can predict the success of cochlear implantation: A last decade review - Binos, Paris; Polemikou, Anna; Loizou, Elena (My University, 2018)
We sought to identify potential communication markers predicting the success of cochlear implantation, that might be observed within the first year of life. According the last ten years literature review volubility can be considered as a potentially important vocal measure predicting later language development.
Keywords: Volubility; Cochlear implants; Early vocalization; Auditory perception